Choreographing Well-Being: The Predictive Role of Self-Compassion on Life Satisfaction—A Therapeutic-Based Art Pedagogy Perspective in Recreational Dance - Aglaia Zafeiroudi; Thomas Karagiorgos; Ioannis Tsartsapakis; Gerasimos V. Grivas; Charilaos Kouthouris; Dimitrios Goulimaris (Sports, 2025)
Dance encompasses physical, emotional, and social elements, creating a dynamic platform for the exploration of well-being. As a therapeutic approach, dance movement further applies these dimensions to enhance emotional resilience, foster mindfulness, and improve overall mental health. This study examined the relationship between self-compassion and life satisfaction among 912 recreational dancers (80% female and 20% male) in Greece. Participants completed the Self-Compassion Scale and Satisfaction with Life Scale. Confirmatory Factor Analysis validated the five-factor self-compassion model, and regression analysis identified predictors of life satisfaction. Self-kindness emerged as a strong positive predictor (β = 0.258, p < 0.001), while isolation (β = −0.307, p < 0.001) and self-judgment (β = −0.083, p = 0.029) negatively predicted life satisfaction. Common humanity (β = 0.064, p = 0.066) and mindfulness (β = 0.004, p = 0.907) showed no significant predictive effect. The model explained 21.7% of the variance in life satisfaction (R2 = 0.217). Small but statistically significant differences in self-compassion dimensions were observed across dance styles. Partner-oriented dancers such as those practicing tango reported slightly higher self-kindness and mindfulness, while ballet dancers showed a small increase in self-judgment and isolation. Life satisfaction remained consistent across styles, highlighting dance’s overall contribution to well-being. These findings suggest that integrating self-compassion training into dance education and psychotherapy, particularly within a Therapeutic-Based Art Pedagogy framework, may contribute to emotional resilience, foster social connection, and promote mental health, positioning dance as a potentially transformative tool for holistic development.